Intermediaries in European law: traces of their liability for lack of intermediated contract fulfilment - Arnau Raventós, Lidia (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
This study aims to identify what elements, present in some way in European private law, allow us to specify what, today, such legislation establishes regarding the liability of intermediaries in the event of non-compliance with the intermediary contract. The attention focuses on the foundation and liability rules. In the absence of general European regulations on the matter, the study aspires, not so much to infer such a general principles from a dispersed and fragmented European regulation, but to identify those spaces in which precisely this lack of European response calls into question and forces internal schemes.